Monitoring Depth of Anaesthesia Using Auditory Brainstem Response: An Exploratory Clinical Study. (March 2014) - Larsson, Catharina; Persson, Emma; Åhlander, Fredrik; Jahr, John; Johansson, Anders
Purpose: Various depth-of-anaesthesia monitors are available, but their trustworthiness is questioned. The aim of this study was to investigate brainstem auditory-evoked potentials during general anaesthesia using a specific audiometry method named SensoDetect Brainstem Evoked Response Audiometry (SD-BERA). Methods: Seven patients with American Society of Anaesthesiologists physical status I and II scheduled for elective orthopaedic surgery were assigned. Brainstem auditory evoked responses were recorded at different stages of anaesthesia. Bispectral index and end-tidal tension of Sevoflurane were measured at the same time. Results: The index (%) from pre-anaesthesia to anaesthesia were significantly reduced 100 [0–0] vs. 53 [49–72], respectively (p=0.0156). At extubation the index were set back to normal level with a significant increase from anaesthetized state, 102 [78–135] (p=0.0156). No significant difference could be observed between pre-anaesthesia and at extubation (p=0.6875). Conclusion: The findings imply that SD-BERA has a potential to measure depth of anaesthesia.